2018
DOI: 10.3390/mi9020082
|View full text |Cite
|
Sign up to set email alerts
|

On the Bipolar DC Flow Field-Effect-Transistor for Multifunctional Sample Handing in Microfluidics: A Theoretical Analysis under the Debye–Huckel Limit

Abstract: We present herein a novel method of bipolar field-effect control on DC electroosmosis (DCEO) from a physical point of view, in the context of an intelligent and robust operation tool for stratified laminar streams in microscale systems. In this unique design of the DC flow field-effect-transistor (DC-FFET), a pair of face-to-face external gate terminals are imposed with opposite gate-voltage polarities. Diffuse-charge dynamics induces heteropolar Debye screening charge within the diffuse double layer adjacent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 65 publications
0
6
0
Order By: Relevance
“…Ji et al [ 15 ] reported a direct numerical simulation of similar dielectrophoretic interactions between deformable particles. Liu et al [ 16 ] proposed a method of bipolar field-effect control of direct current electroosmosis for multifunctional sample handling. Later, Tao et al [ 17 ] used a similar idea to design nanofluidic ion diodes for field-effect control of ion current.…”
Section: Nonlinear Electrokinetic Phenomena (Eight Papers)mentioning
confidence: 99%
“…Ji et al [ 15 ] reported a direct numerical simulation of similar dielectrophoretic interactions between deformable particles. Liu et al [ 16 ] proposed a method of bipolar field-effect control of direct current electroosmosis for multifunctional sample handling. Later, Tao et al [ 17 ] used a similar idea to design nanofluidic ion diodes for field-effect control of ion current.…”
Section: Nonlinear Electrokinetic Phenomena (Eight Papers)mentioning
confidence: 99%
“…Generally, a common substrate in TFTs is glass, which differs from the conventional transistor, where the semiconductor material typically is the substrate, such as a silicon wafer. TFTs include three basic elements: (1) a thin semiconductor film; (2) an insulating layer; and (3) three electrodes (gate, source and drain) [ 7 , 8 , 9 ]. Three basic elements for configuration of TFT have been illustrated clearly in Figure 1 .…”
Section: Introductionmentioning
confidence: 99%
“…Because the ionic charge layer emerges as a result of the applied AC electric field, both the induced free charge and tangential field component are sinusoidal functions of the time variable under Debye-Huckel limit, resulting in time-averaged electroosmosis flow even in a harmonically oscillating field [ 23 , 24 , 25 ]. Later, Bazant and Squires [ 26 , 27 ] indicated that a background electric field can act on its own induced free charge within the Debye layer at a polarizable phase interface, which is genuinely a more accurate physical description of nonlinear electrokinetic phenomena, and they coined the term ‘Induced-Charge Electroosmosis (ICEO)’ to delineate electroosmotic streaming on polarizable or highly-charged solid surfaces immersed in saline solutions, which has incorporated the physical concepts of AC electroosmosis/traveling-wave electroosmosis (ACEO/TWEO) on driving electrodes in standing-wave [ 28 , 29 ]/traveling-wave [ 30 , 31 , 32 , 33 , 34 , 35 ] electric fields, ICEO on bipolar conducting [ 15 , 36 , 37 , 38 , 39 , 40 , 41 , 42 ]/semiconducting [ 43 , 44 ]/dielectric [ 16 , 45 , 46 , 47 , 48 ] materials, and electroosmosis of second kind due to surface-conduction-induced bulk concentration polarization [ 49 , 50 , 51 , 52 ]. This new category of electrohydrodynamic flow shows great advantages in suppressing electrode reactions and bubble productions, as well as actuating faster fluid flows than conventional linear electroosmosis, by virtue of its second-order voltage dependence in time-varying electric fields [ 14 , 53 , 54 ,…”
Section: Introductionmentioning
confidence: 99%